2018
DOI: 10.15244/pjoes/76912
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Controls of Carbon Use Efficiency across China’s Grasslands

Abstract: Understanding the responses of the terrestrial ecosystem carbon cycle and related vegetation growth to intensified global climate change, which has been reported widely, is of great significance [1-3]. For instance, more recent reports have documented that climate change regulates the carbon storage of Europe [4], with both precipitation and temperature affecting carbon storage of the Scots pine forest ecosystems of Poland [5], and the increasing temperature results in the reduction of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…By integrating multiple‐sourced data, this study revealed a phenomenon rarely captured by related studies for the TP, that is, negative and nonlinear responses of the CUEe to warming (Z. Chen et al., 2018; Fu et al., 2016; Hou et al., 2018). It is worth noting that the CUEe declines by a greater magnitude under HW than under LW.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…By integrating multiple‐sourced data, this study revealed a phenomenon rarely captured by related studies for the TP, that is, negative and nonlinear responses of the CUEe to warming (Z. Chen et al., 2018; Fu et al., 2016; Hou et al., 2018). It is worth noting that the CUEe declines by a greater magnitude under HW than under LW.…”
Section: Discussionmentioning
confidence: 77%
“…The TP has also undergone a faster rate of climate warming than the Northern Hemisphere average in recent decades, and warming has emerged as a widely studied ecosystem driver (Qiu, 2008; Y. Zhang, Zhu, et al., 2019). Pioneering studies of CUEc on the TP apply remote sensing observations at a regional scale, and the underlying CUEe mechanisms remain elusive (Fu et al., 2016; Hou et al., 2018). Here, by integrating a manipulative experiment using a warming gradient at a site scale, two EC measurements at a landscape scale and ten synthetic warming experiments and four ecosystem process models at a regional scale, we explored the impacts of warming on the CUEe across the alpine grasslands of the TP.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported a positive relationship between annual CUE and temperature across biomes (Hou, Sun, & Wang, 2018;Piao et al, 2010). One plausible explanation for the positive relationship between CUE and temperature that has been given is that, although rising temperature is generally accompanied by an extension of the GS and an increase in GEP, the accompanying increase in R a is limited by respiration acclimation over a long-term warming period (Piao et al, 2010).…”
Section: Spring (April To May)mentioning
confidence: 89%
“…Soil water is another important environmental condition in altering plant colonization and distribution specially in the arid alpine steppe (Sun et al, 2013;Ma et al, 2017). Soil water conditions can affect soil nutrient supply ability and drive plant succession in alpine steppe (Yang et al, 2013;Hou et al, 2018). For example, low SWC is inhospitable to nitrogen uptake for graminoids which is more nitrophilous (Hou et al, 2018).…”
Section: Habitat Conditions and Root Morphological Traits Determine Pmentioning
confidence: 99%
“…Soil water conditions can affect soil nutrient supply ability and drive plant succession in alpine steppe (Yang et al, 2013;Hou et al, 2018). For example, low SWC is inhospitable to nitrogen uptake for graminoids which is more nitrophilous (Hou et al, 2018). Additionally, even a small variation in SWC may cause a remarkable difference in both seed germination and seedling survival, which consequently affects the individual amount and composition of plant community (Ma et al, 2017).…”
Section: Habitat Conditions and Root Morphological Traits Determine Pmentioning
confidence: 99%